Pengembangan E-LKPD Menggunakan Aplikasi Wizer.Me Pada Mata Pelajaran IPAS Materi Transformasi Energi Di Sekitar Kita - Siti Nur Elisa, Siti Nur Elisa (UNIB Press, 2023)
This research is Research and Development (RnD), with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). This study aims to develop and determine the feasibility of E-LKPD using the Wizer.me application. The feasibility of E-LKPD is proven through the results of expert validation and student responses. The validation results of media experts, linguists, and material experts stated that the E-LKPD using the Wizer.me application was very feasible to use with the results of data analysis from the completed questionnaire obtaining a percentage of 94.2% from media experts, 100% from linguists, and 96% from material experts, which means the product being developed is really worth testing out. Based on a limited trial conducted on students in class IV-A, as many as 26 students received a very good response with a percentage of 97%. Thus it can be concluded that the development of E-LKPD using the Wizer.me application in the Natural Sciences subject matter of energy transformation around us is very feasible to use in the learning process. The results of the research are expected to provide new knowledge regarding the use of electronic-based student worksheets using the Wizer.me application